Thermal Properties of Solids – Theoretical Basis, Research Methods and Selected Results of Proprietary Research - Janusz ZMYWACZYK (Właściwości cieplne ciał stałych – podstawy teoretyczne, metody badań, wybrane wyniki badań własnych, 2021)
This paper refers to an inaugural lecture prepared by the author for the inauguration of the New Academic Year 2020/2021 at the Faculty of Mechatronics, Armament and Aerospace of Military University of Technology (MUT) in Warsaw (Poland) on 2 October 2020. It presents the origins of research into thermal properties of solids since the mid-1970s by the employees of the thermodynamic research unit at the Department of Aerodynamics and Thermodynamics, followed by the basic modalities of heat transfer, theoretical foundations of thermal expansion, specific heat, thermal conductivity and thermal diffusivity of solids. The measuring apparatus created as a result of proprietary research studies and purchased from market-leading manufacturers is shown with a selection of results from the research into the thermal properties of solids, which are largely the outcome of the application our own research procedures.
Keywords: Właściwości cieplne ciał stałych